SMS Advertising : Young Working Consumers’ Attitude Towards Receiving SMS Advertising / Faizul Ilham Mohd Nasir - Mohd Nasir, Faizul Ilham (2014)
Technological advancements have provided various new mediums for advertising to consumers and have further allowed organizations to better reach consumers with regards to the frequency and impact of advertising. Advertisers have to be more creative in the formulation of advertisements and selection of advertising mediums so as to gain the attention of their target market. The need to create new mediums for advertising has lead to the creation of new age media such as inter alia, short message service (SMS) advertising. Before this medium can be effectively used to reach young working consumers in North Kuching specifically surrounds the area of CIMB Bank Berhad, Jalan Khoo Hun Yeang branch, the attitude of consumers towards SMS advertisements need to be determined. This study therefore focuses on investigating the young working consumers’ attitude towards SMS advertising and a research framework was constructed to identify relevant factors affecting consumers’ attitude towards SMS advertisements and users actual behavior.